Olderpreneur – future market challenges - Krzyminiewska, Grażyna (Bulletin of Geography. Socio-economic Series, 2021)
Abstract Building competitiveness of the economies of the countries with the most advanced population aging processes becomes a significant economic and social challenge in the contemporary society. In this paper, focus turns to entrepreneurship among the older generation. The following matters will be discussed: the essence of the phenomenon of the olderpreneur; the nature of entrepreneurship of older people in the global and European scale, with special emphasis on Poland; the challenges for the future labour market arising out of the demographic processes taking place. The content of this paper is in line with economic and social analysis, using the sociological and economic achievements, and is based on the existing sources and the results of own research. Desk research and descriptive and comparative analysis are used in the presentation of the issues addressed. Study of the relevant literature critical review was carried out and secondary sources were used.